Plant Secondary Metabolites Inhibit Cancer by Targeting Epidermal Growth Factor Receptor (EGFR): An Updated Review on their Regulation and Mechanisms of Action - Jamal, Adil; Arif, Amina; Shahid, Muhammad Naveed; Kiran, Shumaila; Batool, Zunaira (Asian Pacific Journal of Cancer Biology, 2025)
Cancer is an exceedingly pervasive disease currently, with approximately 14 million individuals diagnosed every year. The lifestyle and environmental changes are the most widespread causes of cancer. There are numerous cancer treatments available, including chemotherapy, radiotherapy, and hormone therapies. However, these procedures have adverse effects. In such circumstances, plant-based therapies have shown increased efficacy. Plant secondary metabolites such as alkaloids, polyphenols, cannabinoids, and flavonoids have anti-inflammatory, anti-tumor, and anti-proliferative properties, making them ideal candidates for cancer treatment. They inhibit major signaling pathways like MAPK, EGFR, VEGF, Ras/Raf, NF-kβ, induce necrosis, apoptosis, ferroptosis, and cause cell cycle arrest. Phytochemicals together with nanomedicines have a better possibility of eliminating malignant cells. They impede mitophagy while regulating Caspase-dependent cascades. Molecular investigation has revealed that they influence DNA repair, liposomal activities, and the phagocytosis process. The highlights of this review encompass how chemotherapeutic agents induce multidrug resistance, and phytochemical-based cancer treatments and their mechanisms of action, including how they rejuvenate cell damage and eliminate tumor cells from the body.